A NEED ANALYSIS FOR TEACHING LEADERSHIP SKILLS TO MEDICAL STUDENTS IN PAKISTAN - Riaz, Salman; Tabassum, Misbah (Journal of Ayub Medical College Abbottabad, 2021)
Background: Perspectives of practicing medicine have rapidly changed due to global shift and interconnectedness. Doctors who do not develop their leadership skills may lack the acumen to make significant choices which enhance the quality and effectiveness of care. Pakistan is one of those countries that have not yet introduced the leadership skills training for undergraduate medical students. Aim of this study was to perform a perceived need analysis for teaching leadership skills to undergraduate medical students in Pakistan. Methods: The study was designed using phenomenological approach to gain detailed insights into what the research participants think about leadership. Qualitative methods were used for data collection and analysis. Data were collected from fourteen medial students in their 3rd, 4th and 5th year and eight staff members of medical colleges through semi-structured interviews and focus group discussion respectively. Thematic analysis was used for data analysis. Results: Participants agreed that leadership skills are necessary for successful medical practice and can be learnt with timely and proper guidance. Need to introduce a leadership curriculum for undergraduates was recognised to acquire skills for pressure handling before entering clinical practice. The view was common that doctors in Pakistan are good at clinical skills but have no or weak leadership skills, affecting their clinical practice. Transformational leadership that encompasses behaviours resulting in empowering, inspiring and challenging the followers to make them capable of reaching their full potential was recommended necessary for developing successful physician leaders. Simulated scenarios, case-based learning, lecture-based modules and peer-led case discussions were suggested as the useful methods for course delivery. Formative method of assessment with feedback was suggested rather than summative assessment. Conclusion: There is a perceived need to introduce a leadership course in early years of medical curriculum of Pakistan, as participants acknowledge the importance of clinical leadership and depicted the preparedness to have leadership education implemented in the curriculum. Keywords: Curriculum; Education, Medical; Undergraduate; Leadership; Students, Medical